2005
DOI: 10.1152/ajpheart.00570.2005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring surface potential components necessary for transmembrane current computation using microfabricated arrays

Abstract: This study was designed to test the feasibility of using microfabricated electrodes to record surface potentials with sufficiently fine spatial resolution to measure the potential gradients necessary for improved computation of transmembrane current density. To assess that feasibility, we recorded unipolar electrograms from perfused rabbit right ventricular free wall epicardium (n = 6) using electrode arrays that included 25-microm sensors fabricated onto a flexible substrate with 75-microm interelectrode spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Use of selected electrodes for stimulation and recording would allow implementation of our method for microimpedance measurements. In myocardial tissue, we envision positioning of microfabricated arrays onto tissue following the approach we recently described (58). In that report, we used microfabricated sensors with spacing on the size scale of individual myocytes that were packaged in flexible assemblies that included adjacent signal conditioning to facilitate highquality interstitial potential difference recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Use of selected electrodes for stimulation and recording would allow implementation of our method for microimpedance measurements. In myocardial tissue, we envision positioning of microfabricated arrays onto tissue following the approach we recently described (58). In that report, we used microfabricated sensors with spacing on the size scale of individual myocytes that were packaged in flexible assemblies that included adjacent signal conditioning to facilitate highquality interstitial potential difference recordings.…”
Section: Discussionmentioning
confidence: 99%
“…This may further improve the SL measurement technique, defined as the second spatial derivative of the field potential on the heart surface, which was reported to be superior to the unipolar electrogram (potential difference between the exploring electrode to the reference electrode) for the detection of local activation during ventricular fibrillation [19,20]. The in-vivo transmembrance current density (1m) calculated using the Surface Laplacian technique may be improved as suggested in previous simulation studies [21].…”
Section: Purposementioning
confidence: 94%
“…It has been reported that the Surface Laplacian electrogram is superior to the unipolar electrogram in detecting local activation time during VF [20,22,23]. Also, SL morphologies can determine the activation block and wavefront initiation, and improve the transmembrance current density calculation [23].…”
Section: Significance Of the Studymentioning
confidence: 99%
See 2 more Smart Citations